Otter doesn't know - Fritz, Andrea (Fritz, Andrea. Coast Salish tales., 2023)
"In this picture book featuring Coast Salish art and traditional storytelling techniques, a salmon and an otter learn to help each other even though they don't have all the answers. Some hul'q'umi'num' words throughout text (not a dual-language book)."--